Evaluation of the impact of COVID-19 pandemic on hospital-acquired infections in a tertiary hospital in Malaysia - Ismaeil, Rehab A.; Fata Nahas, Abdul Rahman; Kamarudin, Norhidayah; Usman, Abubakar Abubakar; Mat Nor, Mohd Basri; Nik Mohamed, Mohamad Haniki (SPRINGER, 2023)
Background Infection prevention measures are the gold standard for preventing the spread of hospital-acquired infections (HAIs). COVID-19 pandemic caused major disruptions in infection prevention measures, and this has implications on the rate of HAIs. This study assessed the impact of COVID-19 pandemic on the rate and the types of HAIs at Sultan Ahmed Shah Hospital.